2018
DOI: 10.1097/ico.0000000000001628
|View full text |Cite
|
Sign up to set email alerts
|

Descemet Membrane Endothelial Keratoplasty After Penetrating Keratoplasty: Features for Success

Abstract: DMEK is a viable option for cases of failed PKP. DMEK failure after PKP might be associated with lower visual acuity before DMEK surgery, higher number of rebubble interventions, and manual descemetorhexis rather than femtosecond laser-enabled DMEK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
4
25
0
3
Order By: Relevance
“…1). This observation was also made by other authors (Gundlach et al 2015;Einan-Lifshitz et al 2018;Pierne et al 2019).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1). This observation was also made by other authors (Gundlach et al 2015;Einan-Lifshitz et al 2018;Pierne et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Compared to other studies, we report an acceptable survival rate of 65.4% after two and a half years. Einan‐Lifshitz et al (2018) reported a survival rate of 57% after 3 years, Pasari et al (2019) 80% after 3 years and 76% after 4 years. Possible explanations for the low graft survival rate in our cohort may include (i) the complex initial situation in most eyes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual recovery and central pachymetry improvement were relatively fast during the study period (Table 2). Those favorable clinical outcomes are consistent with other studies as well [16,18,22]. The visual recovery with DMEK under failed PK contrasts sharply with the delayed and unpredictable visual rehabilitation after re-PKP [29].…”
Section: Discussionsupporting
confidence: 90%
“…Common conclusions have emerged from multiple previous studies regarding the results of DMEK after PKP compared to primary DMEK [16,18,19,22,23], including higher rebubbling rates, higher endothelial cell density loss, higher late graft failure rates and more demanding surgical technique. Furthermore, glaucoma ltering surgeries, which are probably more prevalent in post-PKP eyes, are considered a signi cant risk factor for late graft failure, probably as a result of altering the microenvironment in the aqueous humor which accelerates endothelial cell loss [24].…”
Section: Discussionmentioning
confidence: 99%